2020
DOI: 10.1155/2020/1936385
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Values of MANF Expression in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors, and its prognosis is still poor. Mesencephalic astrocyte-derived neurotrophic factor (MANF) plays a key role in endoplasmic reticulum stress. ER stress plays a key role in HCC carcinogenesis. To confirm the clinical and prognostic value of MANF in HCC, we investigated the expression level of MANF in HCC as recorded in databases, and the results were verified by experiment. Survival analysis was probed by the Kaplan–Meier method. Cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, it remains unknown whether the expression of ITGB2 is elevated in hepatocellular carcinoma. He et al 39 showed that MANF was overexpressed in HCC, but Liu et al 40 found that the mRNA and protein levels of MANF were lower in HCC tissues than in adjacent non-cancer tissues. Thus, we hypothesize that the differential expression of MANF is associated with liver cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains unknown whether the expression of ITGB2 is elevated in hepatocellular carcinoma. He et al 39 showed that MANF was overexpressed in HCC, but Liu et al 40 found that the mRNA and protein levels of MANF were lower in HCC tissues than in adjacent non-cancer tissues. Thus, we hypothesize that the differential expression of MANF is associated with liver cancer.…”
Section: Resultsmentioning
confidence: 99%
“…21 At present, various candidate biomarkers or discriminative models had been proposed, and most of them were concentrated at end-stage liver diseases, especially on HCC. 22,23 controls. Finally, our findings were verified through an independent validation cohort of 230 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression prognostic signature for high-grade serous ovarian cancer was investigated by resampling/cross-validation method with Cox regression analysis followed by Kaplan–Meier analysis and log-rank testing [ 62 ]. Similarly, He et al [ 63 ] probed the survival analysis of the expression level of MANF in HCC using the Kaplan–Meier method. In addition, Cox regression models were used to ascertain the prognostic value.…”
Section: Discussionmentioning
confidence: 99%